Synthesis, Crystal Structure, and DFT Calculations of 1,3-Diisobutyl Thiourea - Ataf A. Altaf; Adnan Shahzad; Zarif Gul; Sher A. Khan; Amin Badshah; Muhammad N. Tahir; Zafar I. Zafar; Ezzat Khan (Journal of Chemistry)
1,3-Diisobutyl thiourea was synthesized and characterized by single crystal X-ray diffraction. It gives a monoclinic (α = γ = 90 and β  ≠ 90) structure with the space group P21/c. The unit cell dimensions are a = 11.5131 (4) Å, b = 9.2355 (3) Å, c = 11.3093 (5) Å, α = 90°, β = 99.569° (2), γ = 90°, V = 1185.78 (8) Å3, and Z = 4. The crystal packing is stabilized by intermolecular (N–H⋯S) hydrogen bonding in the molecules. The optimized geometry and Mullikan's charges of the said molecule calculated with the help of DFT using B3LYP-6-311G model support the crystal structure.